Bio-graded recycling for hot asphalt mixtures with high RAP content considering freeze-thaw - He, Liqiang; Li, Yafei; Xia, Moxuan; Liu, Rui; Gu, Qiutai; Luo, Xiangyu; Zhang, Xing (Frontiers in Materials, 2024)
This paper investigates the effects of freeze-thaw cycles on the performance of asphalt mixtures containing 60% rejuvenated asphalt pavement (RAP). Two rejuvenation processes, traditional and biograded recycling, are compared regarding high-temperature performance, low-temperature performance, dynamic stability, flexural tensile strength, split tensile strength, water stability, and fatigue performance after various freeze-thaw cycles. The results indicate that bio-graded rejuvenation, compared to traditional rejuvenation, effectively enhances the high-temperature performance, lowtemperature performance, water stability, and fatigue performance after freeze-thaw cycles. Both rejuvenations initially meet the dynamic stability requirements but show a decreasing trend with increasing freeze-thaw cycles, with traditional rejuvenation exhibiting more severe degradation. The flexural tensile strength initially exceeds that of conventional asphalt mixtures but decreases significantly with freeze-thaw cycles, especially in traditional rejuvenation. Additionally, freeze-thaw action increases the internal void ratio, affecting water stability and anti-freezing ability, particularly in traditional rejuvenated mixtures. These findings underscore the impact of freeze-thaw cycles on rejuvenated asphalt mixtures and emphasize the importance of innovative rejuvenation techniques for sustainable pavement.